2000
DOI: 10.1093/humrep/15.3.616
|View full text |Cite
|
Sign up to set email alerts
|

Embryo transfer under ultrasound guidance improves pregnancy rates after in-vitro fertilization

Abstract: Between October 1998 and January 1999, we examined the influence of ultrasound guidance in embryo transfer on pregnancy rate in 362 patients from our in-vitro fertilization (IVF)-embryo transfer programme. These patients were prospectively randomized into two groups: 182 had ultrasound-guided embryo replacement, and 180 had clinical touch embryo transfer. There were no statistically significant differences between the two groups with respect to age, cause of infertility and in the characteristics of the IVF cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(99 citation statements)
references
References 25 publications
2
86
0
4
Order By: Relevance
“…The importance of this step has been emphasized by the fact that different providers at the same institution may have disparate pregnancy rates after ET (8,9). Other variables affecting pregnancy include the ease of ET (7,10,11), presence or absence of blood on the transfer catheter (12), type of catheter used (13), technique used to perform the transfer (14)(15)(16), and experience of the physician (17).…”
mentioning
confidence: 99%
“…The importance of this step has been emphasized by the fact that different providers at the same institution may have disparate pregnancy rates after ET (8,9). Other variables affecting pregnancy include the ease of ET (7,10,11), presence or absence of blood on the transfer catheter (12), type of catheter used (13), technique used to perform the transfer (14)(15)(16), and experience of the physician (17).…”
mentioning
confidence: 99%
“…Recently, ultrasound-guided embryo transfer has been reported to improve the clinical pregnancy rate after IVF. For example, the clinical pregnancy rate among those undergoing embryo transfer with ultrasound guidance has been reported in the range of 38.4-50%, considerably higher than the 25.4-33.7%, reported for those embryo transfer was not assisted by ultrasound (4)(5)(6)(7)(8). Conversely, one study did not show any statistical difference in the pregnancy rate between the ultrasound-guided group (26.0%) and the nonultrasound-guided group (22.5%) (9).…”
Section: Introductionmentioning
confidence: 81%
“…Several studies have recently analyzed variables affecting successful ET such as US-guided ET, mock transfer, type of catheter, loading the catheter, blood or mucus effects, retained embryos, uterine contractions, and facility of the procedure. Studies which evaluated the effect of US-guided ET indicated that US-guided ET appears to improve IVF success and is significantly associated with increased PRs [5][6][7][8]. However, during US-guided ET the ultrasonographic visualization of newer ET catheters and air bubbles, an identifier of the position of the embryos, is one of the most important developments regarding ET technique.…”
Section: Discussionmentioning
confidence: 99%
“…A targeted successful ET prevents endometrial injury and the induction of uterine contractions; it protects embryos and places embryos in an optimal position within the uterine cavity, thus maximizing embryo implantation. Ultrasound (US)-guided ET can overcome adverse effects including endometrial injury and the induction of uterine contractions during ET and it can determine ET depth and the location of air bubbles [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%